Immunological Role of IL-3, IL-22 and Some Physiological Markers in Iraqi Patients with Chronic Kidney Disease - Hamid, Rehab Harith; AL-Jumaily, Rakad M. Kh. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
Chronic kidney disease (CKD) is a global health issue that is linked to early death and low quality of life. Management in its early phases may lead to better health results. Chronic inflammation related to advanced CKD, as indicated by higher levels of different pro-inflammatory cytokines or impacted levels of acute-phase proteins. This study was carried out in order to assess the roles of interleukins (IL-3 and IL-22), some kidney functions, complete blood count (CBC) and erythrocyte sedimentation rate (ESR) in CKD progression. Commercial enzyme linked immunosorbent assay (ELISA) kits were utilized to calculate interleukin (IL-3 and IL-22) levels in the serum of 60 patients with CKD (age range 20-87 years) and 30 age-matched healthy group. The levels of ESR, CBC, creatinine, urea, uric acid and albumin were also measured. The results showed a significant rise in IL-3 and IL-22 in CKD patients in comparison to healthy controls. CKD Patients were exposed to high levels of some CBC parameters and ESR and there was a significant difference in contrast to group of healthy control. There was a significant rise in creatinine and urea levels in CKD patients compared to healthy controls. The level of albumin was reduced in patients diagnosed with CKD and there was a significant difference between CKD patients and healthy controls. However, the level of uric acid increased in patients diagnosed with CKD but there was no significant difference between patients diagnosed with CKD and healthy group. There is a possible role of interleukins IL-3 and IL-22 in the usage of them as biomarkers for the progression of CKD.